LSTM-Powered Failure Forecasting: Boosting Battery Production Efficiency with Machine Learning - Ishii, Shinichi; Moxotó, Ana Cláudia de Araújo; Mota, Edjard (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
The growing adoption of Artificial Intelligence and machine learning in the industry aims to optimize processes and support decisions. In the electronics sector, electrical tests on components such as battery boards generate vast volumes of data that are often underutilized, while recurrent failures increase costs and affect productivity. This work proposes a predictive model based on recurrent neural networks to predict failures in battery boards from the analysis of historical test data. In our methodology, we first removed outliers and missing values. Then, we developed two recurrent neural network models, LSTM and GRU, to evaluate which would perform better as a prediction model. The results demonstrated that the LSTM 1 and GRU 1 models effectively generated predictions. Failure predictions, such as the 11 identified in the subsequent five days for the Operating Current variable, provide valuable strategic insights. This approach enables managers to make more assertive decisions and implement preventive actions, such as the early replacement of consumables, in order to reduce input costs and minimize unplanned downtime, optimizing efficiency in manufacturing systems.